2014
DOI: 10.1097/wnr.0000000000000085
|View full text |Cite
|
Sign up to set email alerts
|

miR-125b promotes cell proliferation by directly targeting Lin28 in glioblastoma stem cells with low expression levels of miR-125b

Abstract: MicroRNAs (miRNAs) are small noncoding RNA molecules that regulate protein expression by cleaving or repressing the translation of target mRNAs. Our previous studies have revealed that miR-125b is a typical overexpressed miRNA in human primary glioblastoma stem cells (GSCs). Here, we report that miR-125b was also found to be significantly underexpressed in three primary GSCs. Characterization of the effects of the underexpressed miR-125b in GSCs showed that elevated levels of miR-125b inhibited cell growth and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The self-renewal capacity and differentiation potential are hallmarks of stem cells ( 24 ). In the past few years, miR-125b was shown to be an important factor involved in stem cell development by regulating the differentiation of stem cells ( 19 , 20 , 27 ). To evaluate the effect of miR-125b-2 on the direction of ESC differentiation, transfected and control ESCs were cultured in suspension for four days to form EBs ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…The self-renewal capacity and differentiation potential are hallmarks of stem cells ( 24 ). In the past few years, miR-125b was shown to be an important factor involved in stem cell development by regulating the differentiation of stem cells ( 19 , 20 , 27 ). To evaluate the effect of miR-125b-2 on the direction of ESC differentiation, transfected and control ESCs were cultured in suspension for four days to form EBs ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…There is much less known about the roles of miRNAs in mature glia. In glioma-derived stem cells, low miR-125 levels lead to increased proliferation due to a change in Lin-28, a target of miR-125b 50 . For the other mGliomiRs, miR-135a 40 51 , miR-23a 45 , and miR-99a 40 have been reported in astrocytes as well as for Schwann cells in the sciatic nerve along with miR-100 48 , indicating that these miRNAs could be common among glia.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of Lin28 could lead to decreased level of mature miR-363, implying that Lin28 functioned as a positive regulator of miR-363 biogenesis [34]. Additionally, Lin28 could differentially promote and inhibit specific fates of cells by inhibiting miR-302d with its CSD domain [35], miR-125b could efficiently reduce Lin28 protein levels via directly binding to the 3′-UTR region of the Lin28 mRNA [36]. Intriguingly, Willbert et al have reported that Lin28 directly enhances its own expression level by binding to sites within its 3′UTR, revealing a mechanism of positive feedback regulation by Lin28 [37].…”
Section: Molecular Mechanisms Of Lin28 and Its Two Pathwaysmentioning
confidence: 99%